2020
DOI: 10.1177/1457496920935018
|View full text |Cite
|
Sign up to set email alerts
|

Glenohumeral osteoarthritis: an overview of etiology and diagnostics

Abstract: Background and Aims: Osteoarthritis (OA) is the world’s most common joint disease and there is currently no cure. Glenohumeral osteoarthritis (GHOA) accounts for an estimated 5% -17% of patients with shoulder complaints. The etiology of GHOA is multifactorial, and we review the various non-specific and specific risk factors and further sub-classify them into local and systemic factors. Materials and Methods: Data for this review article were identified by searches of MEDLINE, PubMed, and references from releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 69 publications
2
65
0
9
Order By: Relevance
“…Some studies have suggested that individuals with high BMI might be with increased joint load and therefore it accelerates the aging of the articular surface, leading to the occurrence and aggravation of osteoarthritis. 21 In addition, obesity can induce the development of inflammation by increasing the intermediates produced by lipid metabolism, leading to osteoarthritis. 22 However, more researches are need for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that individuals with high BMI might be with increased joint load and therefore it accelerates the aging of the articular surface, leading to the occurrence and aggravation of osteoarthritis. 21 In addition, obesity can induce the development of inflammation by increasing the intermediates produced by lipid metabolism, leading to osteoarthritis. 22 However, more researches are need for further study.…”
Section: Discussionmentioning
confidence: 99%
“…63 64 As age increases from 40 to 80 years, shoulder OA prevalence increases from 1.8% to 27.5%, respectively. 65 Patients who exercise excessively or practice occupations that require over-the-head lifting can also accelerate shoulder OA. Other risk factors include surgeries such as arthroscopic Bankart repairs, fractures, rotator cuff pathology, scapular dysmorphology, inflammatory arthritis, and avascular necrosis of the humeral head.…”
Section: Shoulder Osteoarthritismentioning
confidence: 99%
“…Degenerative changes in the glenohumeral joints have been found in up to 17% of patients with shoulder pain, which has increased over the last 40 years [ 11 , 12 ]. The general prevalence of shoulder disease in the elderly is 5–17%, which is lower than that of other degenerative musculoskeletal diseases, including spine, hand, and knee (462 out of 696 (66%) in the spine, 415 out of 692 (60%) in the hand, 265 out of 696 (38%) in the knee, 36 out of 696 (5%) in the shoulder, and 15 out of 686 (2%), respectively) [ 13 , 14 ]. Because symptomatic glenohumeral osteoarthritis (GHOA) is lower than other weight-bearing musculoskeletal OA, the importance of the functional activity to reduce GHOA should be considered to reveal the precise relationship with shoulder OA.…”
Section: Introductionmentioning
confidence: 99%